Microbial Diversity in Subarctic Biocrusts from West Iceland following an Elevation Gradient - Ekaterina Pushkareva; Israel Barrantes; Peter Leinweber; Ulf Karsten (Microorganisms, 2021)
Biological soil crusts (biocrusts) are essential communities of organisms in the Icelandic soil ecosystem, as they prevent erosion and cryoturbation and provide nutrients to vascular plants. However, biocrust microbial composition in Iceland remains understudied. To address this gap in knowledge, we applied high-throughput sequencing to study microbial community composition in biocrusts collected along an elevation gradient (11–157 m a.s.l.) stretching away perpendicular to the marine coast. Four groups of organisms were targeted: bacteria and cyanobacteria (16S rRNA gene), fungi (transcribed spacer region), and other eukaryotes (18S rRNA gene). The amplicon sequencing of the 16S rRNA gene revealed the dominance of Proteobacteria, Bacteroidetes, and Actinobacteria. Within the cyanobacteria, filamentous forms from the orders Synechococcales and Oscillatoriales prevailed. Furthermore, fungi in the biocrusts were dominated by Ascomycota, while the majority of reads obtained from sequencing of the 18S rRNA gene belonged to Archaeplastida. In addition, microbial photoautotrophs isolated from the biocrusts were assigned to the cyanobacterial genera Phormidesmis, Microcoleus, Wilmottia, and Oscillatoria and to two microalgal phyla Chlorophyta and Charophyta. In general, the taxonomic diversity of microorganisms in the biocrusts increased following the elevation gradient and community composition differed among the sites, suggesting that microclimatic and soil parameters might shape biocrust microbiota.